Time Course and Neurophysiological Underpinnings of Metaphor in Literary Context. Issue 1 (2nd January 2019) - Bambini, Valentina; Canal, Paolo; Resta, Donatella; Grimaldi, Mirko
ABSTRACT: Several theoretical proposals tried to account for the meaning open-endedness of metaphors in literature and for the effortful process they trigger in readers. However, very few experiments have tackled the neurophysiological underpinnings of literary metaphor. Here we used Event-Related brain Potentials (ERPs) to explore the temporal dynamics of comprehending metaphors from Italian poems and novels (e.g., grass of velvet ), presented in their original context, as compared with literal expressions (e.g., throne of velvet ). Results evidence a more negative ERP response for metaphors, unfolding in an N400 followed by a sustained negativity over frontal sites, suggesting a long-lasting effort in elaborating figurative meanings. Whereas the N400 might be indicative of lexical/semantic processes typical of metaphors and amplified by the literary context, the sustained negativity might reflect the manipulation of multiple meanings in working memory, possibly responsible for the poetic effect. Interestingly, the late negativity effect is driven by familiarity, with a more negative response for those metaphors that are less familiar. These findings offer material to discuss ideas put forward in pragmatics, literary studies, and cognitive neuroscience of literature, like the condensation of weak implicatures, the foregrounding, and the relation between a metaphor and its context.